1959
DOI: 10.1113/jphysiol.1959.sp006212
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age, body size and lung volume change on alveolar‐capillary permeability and diffusing capacity in man

Abstract: The published figures for diffusing capacity for carbon monoxide (D,O) in normal human lungs show a wide scatter even for the same method. Minimum, maximum and mean values for six or more normal, resting, seated subjects by the single-breath D,0 method have been recently reported as follows:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
9

Year Published

1965
1965
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(74 citation statements)
references
References 14 publications
4
61
0
9
Order By: Relevance
“…Figure 1 shows that KCO and TL,CO are functions of alveolar expansion [5], cardiac output [8], and haemoglobin concentration [9]. The extensive studies of Stam et al [5] have emphasized that with a reduction in alveolar expansion down to 50% TLC the rise of KCO is linear, although earlier studies [4,10] found a steeper rise at VA v50% VA,max. Despite this increase in KCO, the product KCO6VA (i.e TL,CO) falls as VA declines.…”
Section: Within Individualsmentioning
confidence: 86%
See 1 more Smart Citation
“…Figure 1 shows that KCO and TL,CO are functions of alveolar expansion [5], cardiac output [8], and haemoglobin concentration [9]. The extensive studies of Stam et al [5] have emphasized that with a reduction in alveolar expansion down to 50% TLC the rise of KCO is linear, although earlier studies [4,10] found a steeper rise at VA v50% VA,max. Despite this increase in KCO, the product KCO6VA (i.e TL,CO) falls as VA declines.…”
Section: Within Individualsmentioning
confidence: 86%
“…The variation in KCO with VA in normal subjects has been investigated extensively since 1959 [4]; in 1994, Stam et al [5] suggested that in restrictive lung disease values of TL,CO and KCO should be compared with reference values both at the patient's predicted total lung capacity (TLC) and at the lung volume equal to the patient's actual TLC; this suggestion has been endorsed subsequently [1,6,7]. The novelty in the approach of Chinn et al [1] rests on the development of reference values for TL,CO and KCO, which include a term for VA (at TLC) as well as a height term, i.e.…”
mentioning
confidence: 99%
“…As the lung inflates, DM increases (due to unfolding membranes and increasing surface area), while Vc effects are variable (due to differential stretching and flattening of alveolar and extra-alveolar capillaries) [10,[17][18][19][20][21][22][23][24]. The net effect of these changes is that DL,CO tends to increase as the lung inflates.…”
Section: Determinants Of Co Uptakementioning
confidence: 99%
“…The capacity of the lung to exchange gas across the alveolarcapillary interface is determined by its structural and functional properties [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The structural properties include the following: lung gas volume; the path length for diffusion in the gas phase; the thickness and area of the alveolar capillary membrane; any effects of airway closure; and the volume of blood in capillaries supplying ventilated alveoli.…”
Section: Introductionmentioning
confidence: 99%
“…[192] This air pocket represents 8-9% of its body volume, which happens to be very similar to the proportion of lung capacity to body volume in humans. [192,193] Unlike vertebrates, however, insects employing plastron-based respiration rely entirely on passive diffusion of oxygen through water into their breathing bubbles. These insects are therefore constrained in body size: metabolic rates in insects increase more steeply than surface area with increasing mass.…”
Section: Systems For Sub-aquatic Exchangementioning
confidence: 99%